An interdisciplinary strategy to advance systems engineering theory: The case of abstraction and elaboration. Issue 6 (18th August 2020) - Topcu, Taylan G.; Triantis, Konstantinos; Malak, Richard; Collopy, Paul
Abstract: Prior advances in systems engineering (SE) theory were instrumental in defining the discipline and its tools, but are limited in perspective. The SE community needs new theoretical advances to address its existing and emerging sociotechnical challenges. This communication paper is a product of an NSF/SERC/INCOSE funded workshop on theory building in SE with a focus on the use of abstraction and elaboration. The overarching goals of the workshop were twofold. First, to illustrate the nuances and complexities of the theory building process with an emphasis on developing theory about the SE discipline rather than about a particular system of interest. The second goal was to stimulate a new wave of SE theory by providing a set of frames that could be used for formal theory articulation in follow‐up research. The workshop focused on abstraction and elaboration due to their richness and pervasiveness in SE and investigated the concept in two interrelated contexts: (a) the social coordination of design teams and (b) its strategic use during system design. For each research context, we offer a structured guideline for theorizing, and provide an understanding and framing of some of the generalized abstraction and elaboration uses in SE. Research frames articulated in this workshop could serve as the first step for future research on SE theory, which necessitates hypotheses generation, data collection, validation, and refinement.